Normative Anomaly in Governmental Authority: A Doctrinal Analysis of Forest Area Enforcement in Indonesia - Anastasia Rentama Sijabat; Anna Erliyana (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2026)
Indonesia’s Job Creation Law (Law No. 6 of 2023) introduced a widespread legislative practice of designating the generic term “Central Government” as the legal subject for delegated authority in sectoral statutes. This practice generates substantive ambiguity in identifying the specific officeholder (ambtsdrager) responsible for administrative action, thereby undermining administrative accountability across regulatory sectors. This study examines how this authority anomaly persists in non-labor regulatory contexts, taking Presidential Regulation No. 5 of 2025 on Forest Area Enforcement as the principal case study. Using a normative-doctrinal methodology with statutory, conceptual, and case-based approaches, this research assesses the legal validity of the Forest Area Enforcement Task Force through the attribution-delegation-mandate doctrine, Kelsen’s hierarchy of norms, and administrative legal protection principles. The analysis reveals three critical problems: the absence of a clear statutory basis for the Task Force’s authority; substantive inconsistency with Government Regulation No. 24 of 2021 as the sectoral implementing regulation; and structural misalignment with constitutional court jurisprudence on authority specificity. The study proposes a three-layered normative reconstruction encompassing judicial review, legislative revision, and executive reorganization of the implementing structure. These findings contribute to Indonesian administrative law reform discourse and demonstrate that institutional clarity in governmental authority structures is a necessary precondition for preserving the rule of law.